Monitoring Dynamics, Structure, and Magnetism of Switchable Metal-Organic Frameworks via 1 H-Detected MAS NMR - Blahut, Jan; Lejeune, Arthur L; Ehrling, Sebastian; Senkovska, Irena; Kaskel, Stefan; Wisser, Florian M; Pintacuda, Guido (Angewandte Chemie (International ed. in English), 2021)
We present a toolbox for the rapid characterisation of powdered samples of paramagnetic metal-organic frameworks at natural abundance by 1 H-detected solid-state NMR. Very fast MAS rates at room and cryogenic temperatures and a set of tailored radiofrequency irradiation schemes help overcome the sensitivity and resolution limits often associated with the characterisation of MOF materials. We demonstrate the approach on DUT-8(Ni), a framework containing Ni2+ paddle-wheel units which can exist in two markedly different architectures. Resolved 1 H and 13 C resonances of organic linkers are detected and assigned in few hours with only 1-2 mg of sample at natural isotopic abundance, and used to rapidly extract information on structure and local internal dynamics of the assemblies, as well as to elucidate the metal electronic properties over an extended temperature range. The experiments disclose new possibilities for describing local and global structural changes and correlating them to electronic and magnetic properties of the assemblies.
Keywords: metal-organic framework; proton detection; fast magic-angle spinning; DUT-8(Ni); paramagnetic NMR